Day of the Dead : 20 creative projects to make for your party or celebration - Pascual, Paula; Tang, Phillip (Barron's Educational Series, Inc., 2017)
Let yourself be inspired by the rituals, flavors, motifs and costumes of Mexico's Day of the Dead festival. Create your own celebration with these gorgeous handcrafted decorations, stylish makeup designs and accessories, and delicious recipes.